The best American food writing 2023 - Bittman, Mark; Killingsworth, Silvia; Kennedy, Alicia (Food writer); Loeffler, Amy; Von Bremzen, Anya; Wilson, Bee; Lamback, Briona; Hatchett, Caroline; Chin, Curtis; Streitfeld, David; Moran, Grey; Merwin, Hugh; et al. (Mariner Books, 2023)
""In almost any culture, at any time, you can find food writing," writes guest editor Mark Bittman in his introduction. "Food means growing and hardship, and health and medicine, and work and holiday. In its abundance it is a gift and a joy, and in its absence a curse and a tragedy. If a culture has writing, that culture has food writing." The stories in this year's Best American Food Writing are brilliant, eye-opening windows into the heart of our country's culture. From the link between salt and sex, to Syrian refugees transforming ancient Turkish food traditions, to the FDA's crusade on alternative non-dairy milk options, to Black farmers in Arkansas seeking justice, the scope of these essays spans nearly every aspect of our society. This anthology offers an entertaining and poignant look at how food shapes our lives and how food writing shapes our culture" --